Rooted Resistance: Women’s Socio-Cultural Roles in Environmental Conservation in a Patriarchal Society in Northern Uganda - Ruth Piloya Christine; Barakagira Alex; Abaho Anne (International Journal of Global Health, 2026)
Background In Northern Uganda’s patriarchal communities, women play vital yet underrecognized roles in environmental conservation. There is limited research examining the socio-cultural roles women play in society in northern Uganda. This study, conducted in Gulu District, examined the socio-cultural functions performed by women in safeguarding natural resources. Methods This study employed an analytical cross-sectional design involving 395 women aged 18–49 in Gulu District, selected for its patriarchal context. Data were collected using structured questionnaires and analyzed with SPSS, applying descriptive and inferential statistics. Key variables included women’s roles in environmental conservation and barriers to participation. Ethical approval and informed consent were obtained to ensure research integrity. Results The study found that women in Gulu District play vital socio-cultural roles in environmental conservation, particularly as custodians of indigenous knowledge (Mean = 4.42), active participants in tree planting (Mean = 4.11), and conservers of ecosystems (Mean = 4.04). However, their involvement in advocacy (Mean = 3.46) and decision-making (Mean = 3.20) was perceived as limited, reflecting the constraints of a patriarchal society. Additionally, evolving gender roles have negatively impacted women’s engagement, with 47.6% citing excessive domestic workload and 44.1% reporting reduced participation in conservation activities. These findings highlight both the significance of women’s contributions and the structural barriers that hinder their full involvement in environmental governance. Conclusion Despite these challenges, women’s contributions remain central to sustainable environmental stewardship. The study recommends targeted sensitization and training programs to promote gender equality and community acceptance of women’s leadership in environmental governance.
Keywords: Socio-cultural Roles